EFFECTS OF FICUS THONNINGII EXTRACTS ON THE GASTROINTESTINAL TRACT AND CLINICAL BIOCHEMISTRY OF SUCKLING RATS - Dangarembizi, R; Erlwanger, K. H.; Chivandi, E. (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Ficus thonningii is commonly used in traditional medicine across the African continent. Using forty, 6-day old Sprague Dawley rats, we investigated the effects of crude Ficus thonningii extracts on growth, morphology and morphometry of the abdominal viscera, and clinical biochemistry of neonatal rats. The pups were orally gavaged once daily with either low (50 mg.kg-1 b.w), or high (500 mg.kg-1 b.w), doses of aqueous or methanolic F. thonningii leaf extracts while the control received distilled water. After 7, days of treatment, the pups were euthanased and gross morphometric measurements of the abdominal visceral organs were recorded. Samples of the liver, caecum and proximal small intestine were processed for histology. Plasma biochemical parameters were analysed colorimetrically. High methanolic doses of F. thonningii extracts exhibited trophic effects on the stomach while both aqueous and methanolic extracts had trophic effects on the ceacal mucosa of rats. No significant growth-promoting effects were observed in other visceral organs. Histological analysis revealed no mucosal damage or necrosis. Clinical biochemistry parameters were not abnormally altered. There was a significant decrease (p<0.05, ANOVA), in the plasma concentration of non-fasting glucose in the high methanolic group but triglycerides and cholesterol were unaltered. The findings suggest that at low doses, F. thonningii extracts can be safely used without the risk of any disruption in the structural integrity of the neonatal rat GIT, and function of the liver and kidneys.